What Fraction of the Outer Radiation Belt Relativistic Electron Flux at L ≈ 3‐4.5 Was Lost to the Atmosphere During the Dropout Event of the St. Patrick's Day Storm of 2015?. Issue 11 (21st November 2019) - Gokani, Sneha A.; Kosch, Mike; Clilverd, Mark; Rodger, Craig J.; Sinha, Ashwini K.
Abstract: Observations of relativistic energetic electron fluxes in the outer radiation belt can show dropouts, that is, sudden electron flux depletions during the main phase of a geomagnetic storm. Many recent studies show that these dropouts typically involve a true loss of particles, that is, nonadiabatic losses in nature. Precipitation into the atmosphere of relativistic electrons driven into the bounce loss cone, through wave‐particle interactions, is envisaged as one of the primary loss mechanisms. Such precipitation can be studied using ground‐based observations such as VLF narrowband radio waves, due to the deposition of energy into the lower ionospheric D‐region, thereby modifying the subionospheric waveguide. The present study focuses on the dropout event observed during the St. Patrick's Day storm of March 2015. Perturbations lasting several hours were observed in the received VLF amplitude and phase of the NAA transmitter signal measured at Seattle and Edmonton and the NML transmitter signal received at St. John's and Edmonton. All these L ≈ 3–4.5 paths were located on the nightside of the Earth during dropout phase of the storm. Observations of relativistic electron characteristics from Van Allen Probes, and ionospheric perturbation characterization from VLF radio waves, are used to calculate that during the time interval of the dropout event, <0.5% of the relativistic fluxes involved in the dropout event were lost to the atmosphere. This leads to the conclusion that relativistic electron precipitation was not the major contributor to the observed dropout event at L ≈ 4 that occurred during the St. Patrick's Day storm of March 2015. Key Points: A dropout event during the 2015 St. Patrick's Day storm is examined to find the electron flux lost to the atmosphere Clear perturbations in VLF signal amplitude and phase are seen at L ≈ 3–4.5 at the time of the dropout event Less than ~0.5% of the relativistic flux lost at L ≈ 4 during the dropout was due to precipitation into the atmosphere